2005
DOI: 10.1192/pb.29.9.334
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a screening tool for identifying prisoners with severe mental illness

Abstract: Aims and MethodTo develop and evaluate a screening tool based on the observational skills of prison officers to identify adult male prisoners with severe mental illness. The tool was developed from open-ended interviews with officers and diagnostic interviews with prisoners. A case–comparison study was used to evaluate the tool. Fifty prisoners identified using the tool and 50 randomly selected prisoners underwent diagnostic interviews to determine the proportion in each group with severe mental illness.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For example, detainees suspected of experiencing a mental illness by police officers were referred to services for further evaluation (James, 2000;Scott et al, 2009). While prison officers have been found to correctly identify up to 40% of prisoners with severe mental illness (Birmingham & Mullee, 2005), the accuracy of such assessments made by police officers has not been empirically evaluated. The identification of detainees with a mental illness by police can play an integral role in the safety and well-being of detainees by supplementing the work of medical services in custody (Gibbs, 1986;Steadman, McCarty, & Morrissey, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For example, detainees suspected of experiencing a mental illness by police officers were referred to services for further evaluation (James, 2000;Scott et al, 2009). While prison officers have been found to correctly identify up to 40% of prisoners with severe mental illness (Birmingham & Mullee, 2005), the accuracy of such assessments made by police officers has not been empirically evaluated. The identification of detainees with a mental illness by police can play an integral role in the safety and well-being of detainees by supplementing the work of medical services in custody (Gibbs, 1986;Steadman, McCarty, & Morrissey, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] There is limited research, however, into the incidence of physical or mental health conditions in police detainees, and even less into the efficacy of health screening in this setting. A study of police custody detainees in London in the 1990s found that 1.2% showed signs of schizophrenia, affective disorders, and organic conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, persons may develop mental illness while incarcerated. Appropriate identification and placement of mentally ill persons is important in the treatment, follow-up and rehabilitation of these individuals (10,11). Furthermore, many low-and middle-income countries do not have well-developed, formal prison healthcare services (12).…”
Section: Introductionmentioning
confidence: 99%